„Nie chcemy tego ukrywać” – oczami świadków. Sytuacja duszpasterstwa polonijnego w północnej Francji w 1928 roku - Szymański, Józef (Archiwa, Biblioteki i Muzea Kościelne, 2012)
The establishing of the „Polish Catholic Mission in France” on 13 May 1922 gave way to the cooperation and agreement aimed at guaranteeing hundreds of thousands of Polish community in this country proper religious care. In France, all the bishops who had a larger number of emigrants in their diocese were supposed to coordinate their efforts to provide those people with pastoral care. However, as stated by one of the priests, Polish Mission had no legal basis, the reason for its existence was based on a rather problematic agreement between Cardinal Dalbor and Cardinal Dubois, the Archbishop of Paris. Hence, it was not often possible to avoid the tendencies of French Bishops, who were sometimes unfavorably inclined towards national spirit of the Polish emigration. Some French bishops declared their intentions openly in the decree of Bishop Chaptal. Although this circular letter referred to all foreign nations, because of the largest number of Poles in France it was primarily important for the Poles. The presented document exemplifi es Polish priests attempting to stop the process of denationalization of their countrymen - silent scream.